2021
DOI: 10.5423/ppj.nt.09.2021.0139
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis for a Putative Pyridoxal Phosphate-Dependent Aminotransferase Required for Virulence in Acidovorax citrulli

Abstract: Acidovorax citrulli (Ac) is the causative agent of bacterial fruit blotch disease in watermelon. Since resistant cultivars have not yet been developed, the virulence factors/mechanisms of Ac need to be characterized. This study reports the functions of a putative pyridoxal phosphate-dependent aminotransferase (PpdaAc) that transfers amino groups to its substrates and uses pyridoxal phosphate as a coenzyme. It was observed that a ppdaAc knockout mutant had a significantly reduced virulence in watermelon when in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Supplementary Table 1 organizes all plasmids and bacterial strains used in this study. AcΔyppAc was selected via screening the Tn5 insertional mutant library using a previously reported method ( Kim et al, 2020 ; Lee et al, 2021 ). A germinated seed inoculation was used to select virulence-deficient mutants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Table 1 organizes all plasmids and bacterial strains used in this study. AcΔyppAc was selected via screening the Tn5 insertional mutant library using a previously reported method ( Kim et al, 2020 ; Lee et al, 2021 ). A germinated seed inoculation was used to select virulence-deficient mutants.…”
Section: Methodsmentioning
confidence: 99%
“…Another study verified that type IV pili influence twitching motility, surface adhesion, and virulence ( Bahar et al, 2009 ). Quorum sensing genes, ferric uptake regulators, and a putative glycerol-3-phosphate dehydrogenase are required for Ac virulence ( Johnson and Walcott, 2013 ; Lee et al, 2021 ; Liu et al, 2019 ). However, most studies only focus on the group I strains.…”
mentioning
confidence: 99%
“…Five independent experiments with ten biological replicates were conducted per strain. The leaf infiltration experiments were conducted as previously reported ( Lee et al., 2021 ). Briefly, the watermelon seeds were grown in a growth chamber until they reached the four true leaves stage.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, quorum sensing, a cell-to-cell communication system in bacteria that can regulate gene expression, is also a well-known virulence mechanism in gram-negative pathogenic bacteria including Ac (De Kievit and Iglewski, 2000;Wang et al, 2016). Previous studies have also reported that a ferric uptake regulator, yggS family pyridoxal 5'-phosphate binding protein, a bifunctional chorismate mutase/prephenate dehydratase, and a pyridoxal phosphate-dependent aminotransferase contribute to virulence in Ac (Liu et al, 2019;Kim et al, 2020;Lee et al, 2021;Wang et al, 2022). Although several studies have characterized Ac virulence, additional efforts are still needed, as many virulence-related genes in Ac have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…The complete genome sequence of this strain was recently reported (Kang et al, 2021). For comparative proteomic analysis, we used a label-free shotgun proteomic technique, following a previously established protocol (Lee et al, 2021). The strain was cultured in three different liquid media: the Luria Bertani medium (LB; 10 g of tryptone, 5 g of yeast extract, and 10 g of NaCl in 1 l), an hrp inducing medium (HMM; 1 g of (NH 4 ) 2 SO 4 , 0.246 g of MgCl 2 -6H 2 O, 0.1 g of NaCl, 8.708 g of K 2 HPO 4 , and 6.804 g of KH 2 PO 4 in 1 l), and an amylovoran inducing medium (MBMA; 3 g of KH 2 PO 4 , 7 g of K 2 HPO 4 , 1 g of (NH 4 ) 2 SO 4 , 2 ml of glycerol, 0.5 g of citric acid, and 0.03 g of MgSO 4 , and 10 g of sorbitol in 1 l).…”
mentioning
confidence: 99%